PENGARUH PEMAKAIAN BIOFILTER STRUKTUR SARANG TAWON PADA PENGOLAH LIMBAH ORGANIK SISTEM KOMBINASI ANAEROB-AEROB (Studi Kasus : Limbah Tahu Dan Tempe) - Herlambang, Arie (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2001)
Wastewater treatment of a combined anaerobic-aerobic system is secondarywastewater treatment after physical treatment. Basically this wastewater treatment relies on bacteria in degrading pollutants. The use of honeycomb biofilter is to increase specific surface of media for attaching bacteria. Total volume of reactors is 280 liter, made of glass, equipped with two circulating pump and blower in the aerobic zone. The Biofilter is made of plastic, structurally like honeycomb. Its dimension is 28 cm x 25 cm x 30 cm, very light and easy to clean. It takes 14 days for seeding.The reactors were run in four different resident time, namely 7 days, 5 days, 3 days and 1 day. The raw water used in this experiment is wastewater from tofu and fermented soybean cake industries that have BOD around 300 - 500 mg/l. The water is sampled weekly and the results from 1,872 physical and chemical parameters from 144 water samples show that the reactors that using biofilters have better performance than the reactors using no biofilters. The Efficiency process in decreasing BOD value is around 51 - 91 % for resident time one day up to 7 days. Besides such a good relatively high efficiency, the hydraulic loading is around 0,48 - 3,33 m3/m2/ day and BOD loading is around 0, 20 - 0,43 kg BOD/m3/day.